Autologous Expanded Mesenchymal Stem Cell Implantation for Orthopedic Conditions as a Non-Surgical Approach: A Recent Study - Hassan Mubark (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
This article aims to address the best practice in regenerative medicine. In principle, we use autologous expanded mesenchymal stem cells (MSCs) combined with platelet-rich plasma (PRP) in orthopaedic conditions for cartilage and tendon repair as an alternative to surgical intervention. Osteoarthritis (OA) denotes an absolute and usual path for all major traumatic slurs to synovial joints. OA is the most common form of degenerative joint disease and a foremost source of pain and incapacity. Despite the worldwide rise in OA occurrence, there are no effective pharmacotherapies to restore impaired articular cartilage's unique structure and function. Tendon tears never heal naturally due to their poor blood supply, and currently, surgical repair is the only available option to repair symptomatic tears. Accordingly, cell-based, and biological therapies for OA and related orthopaedic conditions grow into flourishing areas of development and research. Autologous MSCs have been tried to manage osteoarthritis and other orthopaedic pathologies for the last two decades, but it remains experimental therapy.